Pola Komunikasi Kepemimpinan Pegawai Badan Narkotika Nasional Kota Surabaya - Siti Jauharotun Nisa’ (Journal of Management, Education and Communication, 2024)
This study aims to examine the communication patterns between leaders and employees at the National Narcotics Agency (BNN) in Surabaya and to identify the leadership style applied by the head of the BNN in Surabaya. The method used in this study is qualitative descriptive research with data collection conducted through direct observation, in-depth interviews, and relevant documentation. The results of the study show that the communication pattern between leaders and employees at the Surabaya City BNN is formal and structured, utilizing digital media such as WhatsApp as the main means of communication. This communication pattern plays a very important role in supporting effective coordination and increasing the overall productivity and performance of the organization. In addition, this study also reveals that the leadership style applied by the head of the Surabaya City BNN includes a structured communication style, an egalitarian style, and a delegative style. These styles are able to create a conducive work atmosphere and support the optimal achievement of organizational goals